PENGARUH SUPERVISI PENGAWAS, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU EKONOMI DI SMA/MA KOTA SOLOK - Asri Neli; bustari muchtar (Program Magister Pendidikan Ekonomi (S2), 2014)
The purpose of this study was to analyze: 1) The effect of Supervision on Work Environment, 2) The effect of Supervision on Work Motivation, 3) The effect of Supervision on Work Performance, 4) The effect of Work Environment on Work Motivation, 5) The Effect of Work Environment on Work Performance, 6) The effect of Work Motivation on Work Performance. The type of this research is the study of descriptive and assosiatif. The population of this research was all of the economics teacher in high school / Madrasah Aliyah kota Solok, amounting to as many as 33 people. The sampling method is Total Sampling. Techniques of data analysis is descriptive analysis, test analysis and hypothesis testing requirements with path analysis. The results of this study found that: 1) Supervision have significant effect on Work Environment, 2) Supervision have significant effect on Work Motivation, 3) Supervision have significant effect on Work Performance, 4) Work Environment have significant effect on Work Motivation, 5) Work Environment have significant effect on Work Performance, 6) Work Motivation have significant effect on Work Performance. In an effort to create a good economic teacher performance and satisfactory, needs improvement efforts are undertaken in the implementation of ongoing supervision activities, creating harmony and comfort in the work, as well as increased work motivation of teachers so that teacher performance can be achieved optimally. . Keywords: Supervision supervisor, Work Environment, Work Motivation and Performance teacher of Economics.